Analisis Kinerja Keuangan dengan Teknik Du Pont System di Kantor Pusat Bank Bjb Syariah - Nur'aeni Nur'aeni; Eni Nuraeni; Widianingsih Dian Yulianti (Ma'soem University, 2023)
The purpose of this study was to determine the financial performance of BJB Syariah Bank for the period 2017-2021 with the Du Pont System Technique. The object of research in this report is the Financial Statements of Bank BJB Syariah for the period 2017-2021. The type of research is descriptive quantitative with secondary data types and uses data collection techniques in the form of documentation and literature study. The results showed that the financial performance of BJB Syariah Bank for the period 2017-2021 with the Du Pont System technique at the ROI ratio, namely in 2017, 2018 and 2019 was 0.50% then decreased in 2020 by 0.45%. This is due to the decline in the NPM value in 2020, which is 68.40%, but the TATO value in 2020 has increased to 0.70 times. In 2021 ROI will get the same value as the previous year, which is 0.45%. This shows that the company is not good at generating profits but can maximize the turnover of its assets.